Triacetonide of Glucoheptonic Acid in the Scalable Syntheses of d-Gulose, 6-Deoxy-d-gulose, l-Glucose, 6-Deoxy-l-glucose, and Related Sugars. - Liu, Z; Yoshihara, A; Jenkinson, S; Wormald, M; Estévez, R; Fleet, G; Izumori, K (American Chemical Society, 2016)
Ease of separation of petrol-soluble acetonides derived from the triacetonide of methyl glucoheptonate allows scalable syntheses of rare sugars containing the l-gluco or d-gulo structural motif with any oxidation level at the C6 or C1 position of the hexose, usually without chromatography: meso-d-glycero-d-guloheptitol available in two steps is an ideal entry point for the study of the biotechnological production of heptoses.